Naturalizing and systematizing evil - Rolston, Holmes, 1932-2025, author; Routledge, publisher (Colorado State University. Libraries, 2003)
Negative evils (disvalues) in natural systems, though real enough to fauna and flora adversely affected, must be fitted into an ecosystemic and evolutionary framework, with both conservation of life and generating and testing of novel life forms. Struggle and stress are as essential as life support. Such genesis is always by conflict and resolution. Life is perpetually renewed in the midst of its perpetual perishing.
Keywords: humans; nature; nonmoral evil; moral evil; moral standards; evolution